Spatial modeling of water pollution parameters using inverse distance weighting in the Batanghari River, Indonesia - Adella Masya Putri; Yaumal Arbi; Suci Handayani; Shinta Rahayu (Universitas Negeri Padang, 2026)
The Batanghari River, one of the largest rivers in Sumatra, Indonesia, serves as a vital transportation corridor and supports domestic, agricultural, and socio-economic activities. Water quality in the middle reaches of the river is associated with increasing anthropogenic pressures, including settlements, agriculture, sand and gravel mining, and domestic waste disposal. This study models the spatial distribution of water pollution parameters in the Batanghari River, Indonesia, using the Inverse Distance Weighting (IDW) method. The river, which serves as the study site, is 2.5 km long, and sampling was conducted at 16 points in Terusan Village, Maro Sebo Ilir District, Batang Hari Regency. The parameters analysed were pH, Total Suspended Solids (TSS), and Chemical Oxygen Demand (COD). pH measurements were conducted in situ, while TSS and COD were analysed in the laboratory. The measured values were evaluated using the Indonesian Class II river water quality specifications in accordance with Government Regulation No. 22/2021. Spatial distribution modelling was performed using the Inverse Distance Weighting (IDW) interpolation method in ArcGIS 10.8, with model performance evaluated via cross-validation using Root Mean Squared Error (RMSE). The results showed that pH values ranged from 6.76 to 6.91 and were within the class II standard limits. Total Suspended Solids (TSS) ranged between 230.12 and 313.93 mg/L, and Chemical Oxygen Demand (COD) ranged between 35.44 and 93.92 mg/L, exceeding the permitted limits. Areas with higher pollution concentrations were associated with settlements and mining activities, as indicated by the spatial distribution map. These findings suggest that IDW can be applied to the spatial representation of water quality and its improvement as an indicator for pollution control and river management.